Phase transformation temperatures and physical characteristics of NiTiCo shape memory alloys produced by arc melting method - Tatar, Cengiz; Kurt, Murat (Springer Heidelberg, 2020)
The effect of cobalt addition with different proportions into Ni50-xTi50Cox x = 2,4, and 6 wt%) shape memory alloys was investigated. The alloys were produced by arc melting method and then some characteristics, including microstructure, phase transformation temperatures, and magnetic properties, were analyzed. Additionally, the determination of the crystal structure on the alloy's microstructural phases, changes in chemical composition proportions, phase transformation temperatures, and magnetization were investigated at room temperature using XRD, SEM-EDX, DSC, and PPMS, respectively. As a consequence of these measurements, the absorbed and released energies and transformation temperatures exhibit an obvious decrease with the increase of Co addition into the alloys. The microhardness results revealed that the second phase of the alloys has higher hardness compared to the matrix phase. Moreover, with the increase of Co addition into the alloy, Gibbs free energy showed a regular increase while elastic energy exhibited irregular changes. The increase of Co addition to the alloys increased the magnetization property of the alloys.
Keywords: Martensitic-Transformation; Thermodynamic Properties; Mechanical-Properties; Microstructure; Parameters; Elements; Kinetics; Cobalt